ANALISIS EFEKTIVITAS DAN AKURASI PUKULAN ATTACK (SMASH) PEMAIN JAKARTA BHAYANGKARA PRESISI DI AJANG GRAND FINAL PROLIGA 2026 - Audea Sella Amelia Salim; Aziz Amrulloh (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Analysis of the Effectiveness and Accuracy of Spike Attacks by Jakarta Bhayangkara Presisi Players in the 2026 Proliga Grand Final. This study aimed to analyze the effectiveness and accuracy of spike attacks performed by Jakarta Bhayangkara Presisi players during the 2026 Proliga Grand Final. The study employed a quantitative approach using a descriptive research method. Data were collected through observation and video analysis of the 2026 Proliga Grand Final using a notational analysis technique. The variables analyzed included Attack Point (Kill), Attack Dig/Opponent Defense, Attack Blocked, and Attack Error. The data were analyzed using descriptive statistics in the form of frequencies and percentages to describe the effectiveness and accuracy of spike attacks. The findings revealed that out of a total of 1,384 attack attempts, there were 603 Attack Points (Kills) (43.57%), 640 Attack Dig/Opponent Defense (46.24%), 80 Attack Blocked (5.78%), and 61 Attack Errors (4.41%). In Game 1, the team performed 668 attack attempts, while in Game 2 the number increased to 716 attempts. Although the number of Attack Points (Kills) increased from 294 to 309, the Attack Dig/Opponent Defense category remained dominant, indicating that most attacks were successfully anticipated by the opponent's defense. Meanwhile, the relatively low percentages of Attack Error and Attack Blocked indicate that the players demonstrated good attack accuracy. Based on these findings, it can be concluded that the effectiveness and accuracy of spike attacks performed by Jakarta Bhayangkara Presisi players during the 2026 Proliga Grand Final were classified as good. Nevertheless, improvements in attack direction variation, ball placement accuracy, and the ability to read the opponent's defensive system are still required to increase the number of Attack Points (Kills) and reduce the opponent's opportunities to successfully defend attacks (Attack Dig/Opponent Defense).